Serial Communication Protocol With Enhanced Properties-Securing Communication Layer for Smart Sensors Applications - Dudak, Juraj; Gaspar, Gabriel; Sedivy, Stefan; Fabo, Peter; Pepucha, Lubomir; Tanuska, Pavol (IEEE sensors journal, 2019)
The essential component of all the control and sensory systems is a communication layer. The MODBUS protocol used in automation and sensory industry defines a simple format of communication using the master/slave principle, although since it originated in the 1970 it has become obsolete. In this paper, is presented the uBUS protocol as an enhancement of the MODBUS protocol. uBUS protocol proposal brings advanced features for today's requirements for embedded applications. Enhancements include address extension to 4079 addresses, adding a new communication mode (group broadcast), delegating selected master features to slave, linking with other communication interfaces, and securing communications layer. The main part of this paper deals with the description of design and implementation of the uBUS communication security. An RSA algorithm that uses asymmetric encryption was used to implement communication encryption. This paper presents a way of implementing such encryption and its effectiveness on various types of microcontrollers implementing uBUS slaves. Since the communication protocol security is designed as a separate layer, it is possible to implement different types of encryption.